Chromatogram Profile of Vigna radiata and Phaseolus vulgaris Related to Chemical Hydrolysis - Muammar Fawwaz (Pharmaceutical Reports, 2022)
Mungbean (Vigna radiate) and red bean (Phaseolus vulgaris) is a type of food containing isoflavone in the form of glycoside (genistin, daidzin, glycitin). Isoflavones are one type of phytoestrogen which have similar chemical structure with estradiol. Therefore, it can be used not only to inhibit but also to prevent many symptoms related to estrogen deficiency. Human body cannot adsorb isoflavone in the glycoside form. In order to make it absorbable, isoflavone should be hydrolyzed to defuse its glycoside chain to be aglycon (genistein, daidzein, glycitein). The aim of this study was to determine the influence of hydrolysis on chromatogram profile of mungbean and red bean. Hydrolysis was conducted by chemical method using hydrochloride acid (HCl). The chromatogram profile was determined by High Performance Liquid Chromatography method (HPLC) using C18 reverse phase column, the mobile phase was methanol : water (7:3), the sample injected automatically as much as 10 ml, the flow rate of 1 ml/min with a temperature of 28°C, at a wavelength of 254 nm. This study showed that chemical hydrolysis successes to remove the glycoside chain in both mungbean and red bean extract.